The Effectiveness of the Voice-Based Arabic Conversation Application as an Interactive Learning Innovation for Non-Arab Speakers: English - Tri Agung Purnama; Muhamad Ikbal Umahani (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to test the effectiveness of voice-based Arabic conversation applications in improving the speaking skills of non-Arab speakers. Using a quasi-experimental design with experimental and control groups, this research involved 20 participants. The experimental group used the application for two weeks while the control group used the conventional method. The results showed significant improvements in the experimental group in the aspects of pronunciation, fluency, comprehension and interactive response, compared to the control group. Qualitative data revealed that the app increased participants' comfort, motivation, and self-confidence. The findings show that this sound-based application can be used as an effective learning medium.